REDESAIN BODI SEPEDA MOTOR LISTRIK BABY GANESHA 1.0 GENERASI II DAN PENGARUHNYA TERHADAP PENURUNAN COEFFICIENT OF DRAG - Muhammad Khoirul Makhbub; I Gede Wiratmaja; Kadek Rihendra Dantes (Jurusan Teknik Mesin Universitas Negeri Surabaya, 2022)
The aerodynamic aspect is an aspect that really considers the force generated by the fluid flow which has an impact on performance and energy consumption while driving. The purpose of this research is to modify the standard design of the baby ganesha 1.0 generation II electric motorcycle so that it gets a design with a smaller coefficient of drag. The need for fluid flow simulation analysis To determine the coefficient of drag, one way of simulation analysis is to use solidwork, solidworks is known to have the speed and accuracy required for a successful analysis. The conceptual research paradigm R2D2 (Reflective, Recursive, Design and Development) is used to conduct research and development. Development (R&D). After the fluid flow analysis process was carried out, it was found that the modified body design of 2 baby Ganesha 1.0 generation II electric motorcycles obtained a Coeficient Of Drag of 0.0372 lower than the standard body design of Baby Ganesha 1.0 generation II electric motorcycles which only had a coefficient value. of drag is 0.0433. Through expert judgment, the modified design of 2 Baby Ganesha 1.0 generation II electric motorcycles received a percentage with a value of 82% with good qualifications.